WIRELESS INTERNET AS A TOOL-FREE ACCESS TO INFORMATION AT THE PUBLIC COLLEGE - Vergara Moncada, Raúl Jesús (2011)
Clearly it is necessary to change the current educational model and evolve into another model where university education adequately addressed the demand but with quality. Given these needs, Wireless Technology can be one of the key elements that help the required transformations. This has been understood that many Peruvian universities with different intensities of use of the Web offer courses, courses and careers completely virtual. Some believe that the inclusion of Wireless Technologies state that replace the role of teacher, which is not true, because with them the teacher has to play an important role as counselor to students are not lost in the search for information, in the management and use of educational materials, guiding them to make the greatest effort of analysis and interpretation and not just the mechanics of copying and pasting. In this context this article aims to highlight the importance of using wireless technologies to optimize the teaching-learning process.